2014
DOI: 10.1210/me.2014-1079
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Complexity of Hematopoietic Stem Cell Regulation in the Bone Marrow Microenvironment

Abstract: Hematopoiesis in vertebrates is sustained over the duration of an organism's lifetime due to strict regulation of the highly hierarchical hematopoietic system, where a few immature hematopoietic stem cells (HSCs) continuously regenerate the entire blood supply, which is constantly being replaced. Although HSCs self-regulate through cell-autonomous processes, they also receive a variety of signals from their microenvironment or niche. Within the microenvironment, HSCs are regulated through both cell-cell intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 100 publications
0
19
0
Order By: Relevance
“…Previous work also revealed that dmPGE2-treated cells have increased levels of cyclic AMP, increased expression of CXCR4 and survivin, decreased apoptosis, and increased homing to the bone marrow stem cell niche (11, 1416, 24, 25, 27). …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous work also revealed that dmPGE2-treated cells have increased levels of cyclic AMP, increased expression of CXCR4 and survivin, decreased apoptosis, and increased homing to the bone marrow stem cell niche (11, 1416, 24, 25, 27). …”
Section: Resultsmentioning
confidence: 87%
“…The ability of PGE2 to promote hematopoiesis has been documented by two types of experiments: (i) ex vivo treatment of hematopoietic stem cells with dmPGE2 improves stem cell engraftment and consequent survival of mice, and (ii) administration of PGE2 or dmPGE2 to sub-lethally irradiated mice accelerates hematopoietic recovery and increases numbers of the short-term subtype of hematopoietic stem cells (11, 1317, 2427). Previous work also revealed that dmPGE2-treated cells have increased levels of cyclic AMP, increased expression of CXCR4 and survivin, decreased apoptosis, and increased homing to the bone marrow stem cell niche (11, 1416, 24, 25, 27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Niche maintenance is dependent on the complex interplay between soluble mediators, intrinsic signaling pathways and microenvironmental signals [62]. Regulation can be modulated by local signaling, by long-distance cues with hormones or by the autonomic nervous system.…”
Section: Diversity Of the Stem Cell Nichementioning
confidence: 99%
“…The balance between self-renewal and differentiation of hematopoietic progenitor cells is tightly regulated by a variety of cells and signals, which include the microenvironment or niche (20). In crayfish, the progenitor cells are located in packed lobules or between lobules, which are surrounded by connective tissue and ECM (21).…”
Section: Discussionmentioning
confidence: 99%